Traditional knowledge of some medicinal plants used for curing veterinary diseases in Parinche valley of Pune district, Maharashtra, India - Chandrakant K. Waghchaure (International Journal of Pharma and Bio Sciences, 2020)
The present paper seeks attention to the traditional knowledge of some medicinal plants used to cure veterinary diseases by the tribal communities in Parinche valley, Pune district, Maharashtra. The valley consist of 43 villages and hamlets occurring in the total area of about 132 sq. km. Parinche is the biggest village and a nodal place in the valley. In the valley, three tribal communities namely Mahadeo-Koli, Dhangar and Ramoshi are found dominant; they are inhabited in remote villages of the valley. These communities are forest dwellers and well acquainted with medicinal properties of plants that occur in their surroundings. The medicinal plant specimens were collected in triplicate form for identification and authentication. Tribal communities are conscious about the health of their cattle and livestock. They are much depending on their domestic animals to substantiate their livelihood. Because of inaccessibility to other places, large cattle population are most dependent on the forest for various remedies; they are rich in the traditional knowledge about the veterinary medicine to cure cattle. Present study provides a detailed ethno-veterinary medicines, representing 24 plant species from 17 families; Among these plants, members of Fabaceae were dominating and mostly used in the traditional veterinary medicines for the bone fracture, wounds, indigestion, scorpion-sting, snakebite, foot and mouth disease, etc. Out of total recipes only one recipe had combination of two plant species while others were alone. To treat various diseases, plant parts such as leaves, seeds and root bark are used. It can be concluded that because of unhygienic conditions and lack of education, the tribal communities are facing veterinary health problems but they overcome it by using local and easily available plants by trial and error methods.